Project-based learning: Design labs in afterschool - Avila, Bruna Fagundes; Silva, Regio Pierre da (Seven Editora, 2023)
This article aims to present teaching practices from Design as a curricular tool that is part of the school shift. These teaching practices have as a method the Learning Based on Projects of Active and Active Learning Tools that use the Student. The context of the research application took place in a public elementary school of the state network in the city of Porto Alegre/RS. The theoretical path was based on the studies of Fontoura (2002), Bender (2014), Bacich and Moran (2018), as well as the concept of participatory design by Sanders and Stappers (2008). It presents main activities developed and in the installed Design studies, being Graphic Design, Design for Permaculture of Product Project and counts on the school of students' experiences, in these practices. A conclusion aimed at teachers who make use of design skills as instruments of education. Furthermore, it is corroborated by studies such as that of Fontoura (2002) that point out as possibilities of design to break out of academia and the formal job market and reach educational environments. DOI:https://doi.org/10.56238/ptoketheeducati-006